Regenerative Endodontic Treatment of an Infected Immature Dens Invaginatus with the Aid of Cone-Beam Computed Tomography - Işıl Kaya-Büyükbayram; Şerife Özalp; Emre Aytugar; Seda Aydemir (Hindawi Limited, 2014)
Dens invaginatus is a developmental anomaly that results in an enamel-lined cavity intruding into the crown or root before the mineralization phase. This report presents regenerative endodontic treatment of a necrotic immature tooth with Oehler's type III dens invaginatus of a nine-year-old female patient. A diagnosis of dens invaginatus (Oehler's type III) and a large periapical lesion was established with the aid of cone-beam computed tomography (CBCT). In the presented case contrary to the classic revascularization protocol, mechanical instrumentation was performed which apparently did not interfere with the regeneration process. After mechanical instrumentation of the invaginated canal by manual K-files, the invaginated canal space was disinfected by triple antibiotic paste followed by blood clot induction from the periapical tissues and the placement of mineral trioxide aggregate. At one-year follow-up, the tooth remained clinically asymptomatic. Radiographic examination revealed complete healing of the periapical lesion. At the 20-month follow-up, the radiographic examination also showed that the open apex was closed and the walls of the root canal were thickened.